Pengaruh Latihan Crocodile Push-Up dan T Push-Up Terhadap Kekuatan Otot Lengan dan Power Otot Lengan - Firmansyah, Firmansyah (Universitas Hamzanwadi, 2022)
The number of samples is 45 people. The type of research used in this research is quantitative with quasi-experimental method. This research design uses Non-Randomize Control Group Pre-test post-test Design, with data analysis using ANOVA. The data collection process was carried out by means of a push-up test and a medicine ball throwing test during the pre-test and post-test. Furthermore, the research data were analyzed using the SPSS 17.0 series. The results showed that there was a significant effect of the crocodile push-up exercise program on arm muscle strength, with an average post-test measurement result of 20.67, which was higher than the pre-test measurement result of 17.27, there was a significant effect. The crocodile push-up exercise program has a significant effect on arm muscle power, with an average post-test measurement of 135.19, which is higher than the pre-test measurement of 117.36. There is a significant effect of the T push-up exercise program. on arm muscle strength, with an average post-test measurement result of 18.60, looks higher than the results of the pre-test measurement of 16.87, there is a significant effect of the T push-up exercise program on arm muscle power, with the results the average post-test measurement is 130.59, it looks higher than the results of the pre-test measurement of 119.77, there is a difference in the effect of crocodile training push-ups and T-push-up exercises on arm muscle strength. With the calculation results show the value of Sig. 000 > = 0.05 in the ANOVA test, so that the crocodile push-up exercise had a better effect than the T push-up exercise and the control group on increasing arm muscle strength. Based on the analysis above, it can be concluded that there is an increase in arm muscle strength and arm muscle power for each group after being given exercise. Crocodile push-up exercise gave a better effect than T push-up exercise and the control group on arm muscle strength and arm muscle power.